Electrochemical Characteristics of Lithium Vanadium Oxide for Lithium Secondary Battery - Kim, Hyung Sun; Cho, Byung Won (KOREAN CHEMICAL SOC, 2010)
The pure crystalline Li(1.1)V(0.9)O(2) powder has been prepared by a simple solid state reaction of Li(2)CO(3) and V(2)O(3) precursors under nitrogen gas containing 10 mol % hydrogen gas flow. The structure of Li(1.1)V(0.9)O(2) powder was analyzed using X-ray diffraction (XRD) and scanning electron microscope (SEM). The stoichiometric Li(1.1)V(0.9)O(2) powder was used as anode active material for lithium secondary batteries, Its electrochemical properties were investigated by cyclic vol tammetry and constant current methods using lithium 161 electrode. The observed specific discharge capacity and charge capacity were 360 mAh/g and 260 mAh/g during the first cycle, respectively. In addition, the cyclic efficiency of this cell was 72.2% in the first cycle. The specific capacity of Li(1.1)V(0.9)O(2) anode rapidly declines as the current rate increases and retains only 30 % oldie capacity of 0.1C rate at 1C rate. The crystallinity of the Li(1.1)V(0.9)O(2) anode decrease as discharge reaction proceeds. However, the relative intensity of main peaks was almost recovered when the cell was charged up to 1.5 V.
Keywords: COMPOSITE ANODE; ION BATTERIES; VANADATE; LI